Global, regional, and national burden of Pediatric and adolescent thyroid cancer from 1990 to 2021: a statistical analysis of prevalence, incidence, and DALYs - Zhang, Rui; Mei, Zhenxin; Feng, Shan; Chen, Zongcun (Frontiers in Oncology, 2025)
BackgroundThyroid cancer is the most common malignant tumor of the endocrine system. Among children and adolescents, cancer ranks as the fourth leading cause of cancer-related deaths. Pediatric and adolescent thyroid cancer is a rare disease characterized by high metastatic and invasive properties. Currently, there remains a notable absence of comprehensive analyses addressing the global disease burden and evolving trends of Pediatric and adolescent thyroid cancer.MethodsThis study used the Global Burden of Disease (GBD) database (1990-2021) to extract three key metrics: prevalence, incidence, and disability adjusted life years, for Pediatric and adolescent thyroid cancer cases. The data were shown as numerical counts and age-standardized counts per 100,000 within a population with 95% uncertainty intervals (UI). It assessed the evolving trends in the burden of thyroid cancer among children and adolescents by employing the EAPC (Estimated Annual Percentage Change) and percentage change metric.ResultsIn 2021, the global prevalence, incidence, and disability-adjusted life-years of pediatric and adolescent thyroid cancer reached 91,313 cases, 10,137 cases, and 60,185 years respectively. These figures show 94%, 91%, and 25.2% increases over 1990 figures. Over the 32-year observation period, all three metrics demonstrated sustained upward trajectories, with EAPC of 1.58 (95% UI: 1.48-1.68) for prevalence, 1.52 (95% UI: 1.42-1.62) for incidence, and 0.08 (95% UI: 0.00-0.15) for DALYs. In the 5 SDI regions, the prevalence and incidence are showing an upward trend, while DALYs rates showed divergent patterns: a marginal increase in low-middle SDI regions (EAPC=0.13, 95% UI: -0.07-0.32) contrasted with declining trends in other regions. A notable shift in disease burden has been observed across different regions, with high prevalence, incidence, and DALY rates moving from high-income to low-income countries. Age and sex-stratified analysis demonstrated that in 2021, the 20-24-year age group accounted for over 50% of global prevalence, incidence, and DALY rates, with females bearing a significantly higher disease burden than males. As for the global trend, there was a positive correlation between SDI and prevalence, but an inverse association between SDI and incidence, and an inverse relation between SDI and DALY rate. Decomposition analysis attributed 70.61% of prevalence changes and 69.9% of incidence variations to epidemiological factors, while population growth accounted for 71.83% of DALY rate alterations.ConclusionDespite the declining prevalence, incidence, and DALY rates in high-income regions, the global disease burden of pediatric and adolescent thyroid cancer continues to rise, particularly among females and within the 20–24 age group. Therefore, implementing targeted interventions in countries or regions with a higher disease burden could contribute to reducing the global disease burden, optimizing resource allocation, and exploring diverse treatment modalities may be pivotal to addressing the issue.